2009
DOI: 10.1111/j.1365-2222.2009.03203.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment and enzymatic digestion on the B cell epitopes of cow's milk proteins

Abstract: Heat treatment reduced the allergenicity of beta-lactoglobulin by inducing conformational changes and by increasing its susceptibility to enzymatic digestion, both of which disrupted B cell epitopes, whereas heat treatment alone did not alter the allergenicity of alpha-casein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 52 publications
4
28
0
2
Order By: Relevance
“…Untreated and heat treated b-Lg samples were partially resistant to pepsin, as shown in their electrophoretic and chromatographic patterns, confirming the results of previous studies (Herman et al, 2007;Mandalari et al, 2009;Morisawa et al, 2009). According to Morisawa et al (2009), b-Lg is partially resistant to pepsin when heat treated at up to 80 C and is almost totally digested when treated at temperatures above 100 C. The polymerization with TG modified the resistance to pepsin: the heat treated and polymerized samples were partially resistant to the enzyme, whereas the samples treated with 0.25 mol L À1 Cys polymerized with 10 U TG g À1 , was digested by pepsin.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Untreated and heat treated b-Lg samples were partially resistant to pepsin, as shown in their electrophoretic and chromatographic patterns, confirming the results of previous studies (Herman et al, 2007;Mandalari et al, 2009;Morisawa et al, 2009). According to Morisawa et al (2009), b-Lg is partially resistant to pepsin when heat treated at up to 80 C and is almost totally digested when treated at temperatures above 100 C. The polymerization with TG modified the resistance to pepsin: the heat treated and polymerized samples were partially resistant to the enzyme, whereas the samples treated with 0.25 mol L À1 Cys polymerized with 10 U TG g À1 , was digested by pepsin.…”
Section: Discussionsupporting
confidence: 91%
“…According to Morisawa et al (2009), b-Lg is partially resistant to pepsin when heat treated at up to 80 C and is almost totally digested when treated at temperatures above 100 C. The polymerization with TG modified the resistance to pepsin: the heat treated and polymerized samples were partially resistant to the enzyme, whereas the samples treated with 0.25 mol L À1 Cys polymerized with 10 U TG g À1 , was digested by pepsin. Such results confirmed that these treatments modified the protein structure, since the access of pepsin to the cleavage sites was modified.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, most of the studies aiming at analyzing the relationship between structure and allergenicity, and particularly the effect of processing on allergenicity of food proteins, generally use very few individual sera from allergic patients [18], [23], [30], [31], even sometimes only one pool of such sera is available [11], [19], [32], [33]. In the present study, a large population of peanut allergic patients from various European countries was involved leading to significant conclusions.…”
Section: Discussionmentioning
confidence: 80%
“…11−13 However, while pepsin stability as a part of an allergenicity assessment would still seem reasonable for the purpose of safety evaluation of most food proteins, we now know that for some allergenic proteins, this approach would be misleading. The milk allergen β-casein (Bos d 8) 7,14,15 as well as the peanut allergen Ara h 1 9,10 have several times been shown to be easily digestible food allergens.…”
Section: ■ Introductionmentioning
confidence: 99%